Development of a Rating System for Digestive System Impairments: Korean Academy of Medical Sciences Guideline - Baik, Seung Hyuk; Lee, Kyung Suk; Jeong, Seung-Yong; Park, Young Kyu; Kim, Hong Soo; Lee, Dong Ho; Oh, Han Jin; Kim, Byung Chun (Journal of Korean medical science, 2009)
A systematic and effective welfare system for people with digestive system impairments is required. In Korea, an objective and scientific rating guideline does not exist to judge the digestive system impairments. Whether the impairments exist or not and the degree of it need to be examined. Thus, with these considerations we need a scientific rating guideline for digestive system impairments to fit our cultural and social background. In 2007, a research team, for the development of rating impairment guidelines, was organized under the supervision of Korean Academy of Medical Sciences. The rating guidelines for digestive system impairments was classified into upper and lower gastrointestinal tracts impairments and liver impairment. We developed objective rating guidelines for the upper gastrointestinal tract, the impairment generated after surgery for the stomach, duodenum, esophagus, and for the lower gastrointestinal tract, the impairment generated after construction and surgery for colon, rectum, anus, and intestinal stomas. We tried to make the rating impairment guidelines to include science, objectivity, convenience, rationality, and actuality. We especially emphasized objectivity as the most important value. We worked to make it easy and convenient to use for both the subjects who received the impairment ratings and the doctors who will give the ratings.